2020
DOI: 10.1002/phar.2472
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Venous Thromboembolism Associated With Tofacitinib and Baricitinib: A Systematic Review and Indirect Meta‐Analysis

Abstract: To conduct a systematic review and meta-analysis investigating the effect of tofacitinib and baricitinib on venous thromboembolism (VTE) risk. Search of PubMed, EMBASE, Web of Science, Scopus, Clini-calTrials.gov, LILACS, and Google Scholar databases to identify controlled observational and clinical trials reporting on adverse effects in patients treated with oral tofacitinib or baricitinib up to July 2020. The outcome measure was occurrence of VTE events. We analyzed 59 studies involving 14,335 patients treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…It is also high for patients receiving estrogen therapy, major surgery, or those with movement disorders ( 97 ). An indirect meta-analysis showed that tofacitinib has better VTE safety characteristics than baricitinib ( 98 ). A clinical study showed that among patients ≥50 years of age and with ≥1 cardiovascular risk factors, patients who received tofacitinib 10 mg twice a day had a higher incidence of pulmonary embolism than patients who received TNF inhibitors ( 99 ).…”
Section: Targeted Synthesis Dmardsmentioning
confidence: 99%
“…It is also high for patients receiving estrogen therapy, major surgery, or those with movement disorders ( 97 ). An indirect meta-analysis showed that tofacitinib has better VTE safety characteristics than baricitinib ( 98 ). A clinical study showed that among patients ≥50 years of age and with ≥1 cardiovascular risk factors, patients who received tofacitinib 10 mg twice a day had a higher incidence of pulmonary embolism than patients who received TNF inhibitors ( 99 ).…”
Section: Targeted Synthesis Dmardsmentioning
confidence: 99%
“…During the limited placebo-controlled periods, no dose-dependent impact on the risk of VTE events was observed in tofacitinib (5 mg vs. 10 mg twice daily), baricitinib (2 mg vs. 4 mg once daily), or upadacitinib (15 mg vs. 30 mg once daily) [ 64 , 65 ]. The meta-analyses for IMIDs (including RA) showed that VTE risk was unlikely to substantially increase in patients receiving JAK inhibitor during the limited placebo-controlled periods [ 66 69 ]. In a stratified and meta-regression analysis, there was no interaction by dose of JAK inhibitors, indication for treatment, or length of follow-up [ 68 ].…”
Section: Vte Events In Ra Patients Receiving Jak Inhibitorsmentioning
confidence: 99%
“…In a stratified and meta-regression analysis, there was no interaction by dose of JAK inhibitors, indication for treatment, or length of follow-up [ 68 ]. In an indirect meta-analysis, the risk of VTE events in tofacitinib-treated patients was lower than in baricitinib-treated patients (OR 0.09, 95% CI 0.02–0.51), suggesting the superior safety profile of tofacitinib to baricitinib [ 69 ]. No increased risk was found for PE during treatment with JAK inhibitors for IMIDs including RA [ 70 ].…”
Section: Vte Events In Ra Patients Receiving Jak Inhibitorsmentioning
confidence: 99%
“…Moreover, in patients with RA treated with upadacitinib, a significantly higher efflux of cholesterol from macrophages was observed, and this was associated with increased HDLs and reduction of CRP (105). Some real-world studies reported increased major cardiovascular events (MACE) and deep venous thrombotic (DVT) events in patients treated with tofacitinib (especially at higher dose) and baricitinib (106) whereas other studies did not support these findings (107,108). Currently, it is not possible to establish if this increased risk is related to specific direct and indirect cytokine blockade, to chemical structure and/or pharmacologic and toxicologic properties of specific JAK inhibitors, to the presence of concomitant diseases, or other factors (e.g., genetic mutations).…”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%